The Role of Subcutaneous Depot Medroxyprogesterone Acetate in Equitable Contraceptive Care: A Lesson From the Coronavirus Disease 2019 (COVID-19) Pandemic. Issue 4 (October 2021) - Burlando, Audrey M.; Flynn, Anne N.; Gutman, Sarah; McAllister, Arden; Roe, Andrea H.; Schreiber, Courtney A.; Sonalkar, Sarita
Abstract : Since the beginning of the coronavirus disease 2019 (COVID-19) pandemic, health care professionals have made swift accommodations to provide consistent and safe care, including emphasizing remote access to allow physical distancing. Depot medroxyprogesterone acetate intramuscular injection (DMPA-IM) prescription is typically administered by a health care professional, whereas DMPA-subcutaneous has the potential to be safely self-injected by patients, avoiding contact with a health care professional. However, DMPA-subcutaneous is rarely prescribed despite its U.S. Food and Drug Administration approval in 2004 and widespread coverage by both state Medicaid providers and many private insurers. Depot medroxyprogesterone acetate users are disproportionately non-White, and thus the restriction in DMPA-subcutaneous prescribing may both stem from and contribute to systemic racial health disparities. We review evidence on acceptability, safety, and continuation rates of DMPA-subcutaneous, consider sources of implicit bias that may impede prescription of this contraceptive method, and provide recommendations for implementing DMPA-subcutaneous prescribing. Abstract : Increasing subcutaneous depot medroxyprogesterone acetate availability and prescribing has the potential to improve contraceptive access, expand patient autonomy, and decrease racial health disparities.